Hubungan Antara Jumlah Fraksinasi Radiasi Terhadap Kejadian Radiodermatitis Pada Pasien Dengan Ca Mamae Yang Menjalani Radioterapi Di RS Kanker Dharmais - Benget Cris Dohma Ati; Yuni Susilowati; Cicirosnita J. Idu (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
Ca mammae disease is the most common cancer in women. One of the therapies given is radiotherapy treatment. All Ca Mammae cases that underwent radiotherapy mostly experienced radiodermatitis both acute and chronic, the amount of radiotherapy fractionation was one of the causes of radiodermatitis. This study aims to determine the relationship between the amount of radiation fractionation and the incidence of radiodermatitis in patients with Ca Mamae undergoing radiotherapy at Dharmais Cancer Hospital. This study uses a quantitative descriptive cross-sectional approach. A sample of 100 respondents with breast cancer who underwent radiotherapy at the Dharmais Cancer Hospital in January 2023. Data was obtained from the patient's medical records. The analysis used is Chi Square. The results showed that the majority were >45 years old (79.0%), had comorbidities (82.0%), normal BMI (84.0%), the number of fractionations was 16-20 times (48.0%), there was radiodermatitis (Grade I-III) as much (64.0%). There is a significant relationship between the amount of radiation fractionation and the incidence of radiodermatitis in patients with Ca Mamae who undergo radiotherapy at the Dharmais Cancer Hospital with a p-value of 0.002 (<0.05). There is a relationship between the amount of radiation fractionation and the incidence of radiodermatitis in patients with Ca Mamae undergoing radiotherapy at Dharmais Cancer Hospital.